Gadget usage pattern and sleep quality among medical undergraduates during COVID-19 lockdown: a cross-sectional study - Vaidya, Manasi S.; Deshpande, Sonal R. (International Journal Of Community Medicine And Public Health, 2021)
Background: The afoot COVID-19 pandemic has covered approximately every edge of the world. Schools and colleges are temporarily shut leading to children being indoors. Thus, gadgets have become an inseparable part of life and govern the daily routine of an individual. The aim of the study was to assess the pattern of gadget usage and sleep quality among medical undergraduates during COVID-19 lockdown. Methods: Present cross-sectional study was conducted amongst 149 medical undergraduates of Shri Vasantrao Naik Govt. Medical College, Yavatmal. Their gadget usage pattern and sleep quality before and during lockdown were measured using a predesigned and pretested questionnaire based on Smartphone addiction scale-short version (SAS-SV) and Pittsburgh sleep quality index (PSQI), administered via the Google forms platform. Results: 139 (93.28%) responses were completely and correctly filled. Smartphone addiction was seen in 71 (51.08%) study subjects. The mean sleep duration before and during lockdown had no significant changes. There was linear positive correlation between SAS-SV score and PSQI score, but the correlation was not statistically significant. Conclusions: The proportion of smartphone addiction amongst medical undergraduates is significantly high and the mean sleep duration is reduced during lockdown.